Rapid visual detection of hepatitis C virus using a reverse transcription loop-mediated isothermal amplification assay. (January 2021) - Hongjaisee, Sayamon; Doungjinda, Natteewan; Khamduang, Woottichai; Carraway, Tanawan Samleerat; Wipasa, Jiraprapa; Debes, Jose D.; Supparatpinyo, Khuanchai
Highlights: RT-LAMP assay was developed for the detection of HCV in a single-closed tube. The assay is simple, rapid, cost-effective, and result can be observed by naked eye. The assay showed a 95.5% sensitivity and 100% specificity with no cross-reactions. The assay could be able to detect 100% of samples with HCV genotype 6. The assay is an alternative tool for point-of-care testing. Abstract: Objectives: The aim was to develop a reverse transcription loop-mediated isothermal amplification (RT-LAMP) assay for the detection of hepatitis C virus (HCV) in a single closed tube. Methods: Plasma samples were collected from 200 HCV-infected patients. HCV-RNA was detected by one-step RT-LAMP processed at 65 °C for 60 min. The amplified products were detected by hydroxynaphthol blue (HNB)-dependent visual method and gel electrophoresis. Specificity was tested against other viruses. Sensitivity was determined using serial dilutions of extracted RNA. Results: The RT-LAMP assay detected 97.5% of HCV-RNA genotype 1, 91.1% of genotype 3, and 100% of genotype 6. The color change was evidenced with the naked eye. The assay demonstrated a clinical sensitivity of 95.5% and specificity of 100%, as well as no cross-reactivity with other viruses (i.e., hepatitis B virus, HIV). The limit of detection was as low as 10 ng per reaction for HCV genotypes 1a and 6, while it was 100 ng for genotype 3a. The assay showed a 100% detection threshold at a viral load of 5.00 log10 IU/mL in the clinical samples tested. Conclusions: This study demonstrated the use of an RT-LAMP assay for the detection of HCV in a simple, rapid, and cost-effective manner, which will be useful in resource-limited settings to allow the identification of individuals in need of HCV treatment.